The role of organizational affiliation in Achieving Strategic Ambidexterity: An Analytical Study of the Sample Opinions of Colleges Council members at Private Universities in the Erbil City - Essa Saeed Ababakir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The Study research aims to determine the levels of organizational affiliation in under study private universities, through their indicators (performance, experience, workload, distributive justice), and so to identify the availability of the dimensions of Strategic Ambidexterity represented by (Exploratory dexterity, Exploitative dexterity, structural dexterity), in addition to knowing the correlation and impact relationships between the two variables. the research problem was diagnosed by raising questions about the correlation and impact relationships between the two variables. In light of the objectives of the research and its problem, a hypothesis scheme was designed to acquire a set of hypotheses from it whose validity was tested through utilizing the statistical program (SPSS). The research community was represented by all college council members in seven private universities in Erbil city, and their number reached (196) individuals, while (88) of them were chosen to express the research sample. Thus, the proportion of the sample's representation of the community reached (9/44), which is an acceptable percentage in the field of behavioral sciences. The research accomplished a set of conclusions, the most important one is the existence of strong correlation and impact relationships between the two variables, so the research recommended the necessity to employ these relationships to serve the under-study universities.